2014 IEEE International Conference on Management of Innovation and Technology 2014
DOI: 10.1109/icmit.2014.6942469
|View full text |Cite
|
Sign up to set email alerts
|

Development assessment and strategy planning in mobile computing industry

Abstract: Mobile computing continues delivering new opportunities for IT industry. Mobile computing not only offers users greater flexibility, but also allows businesses to integrate their IT infrastructure, introduces new services and increases their computing capacity. As a result, mobile computing technology and the related industry are becoming ever more important. However, the scope, development trends and possible strategy of mobile computing industry have so far not been clearly addressed. To fill this gap, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Such research is suggested to address how other emerging technologies are related to business strategies and functional operations. For example, mobile big data has received inadequate attention from strategic considerations and technology adoption theories [7,8,80]. These efforts should involve studies identifying the factors which affect business operations, information processing, and strategy formation.…”
Section: Study Limitations and Further Researchmentioning
confidence: 99%
“…Such research is suggested to address how other emerging technologies are related to business strategies and functional operations. For example, mobile big data has received inadequate attention from strategic considerations and technology adoption theories [7,8,80]. These efforts should involve studies identifying the factors which affect business operations, information processing, and strategy formation.…”
Section: Study Limitations and Further Researchmentioning
confidence: 99%
“…Along with the deregulation of mobile phone manufacturing in 2007, the rise of MediaTek (MTK), a Taiwanese company specializing in turnkey chipset solutions for mobile phone vendors, marked a turning point in shanzhai entrepreneurship (Wang, 2014;Li and Zhou, 2013). MediaTek's turn-key solution not only provided competitive products to giant technology companies, such as Sony and Samsung, it also allowed mid-and smallsized mobile phone vendors to produce high-quality smartphones with much less capital investment and with shorter turnaround times than traditional methods (Chen, 2013;Rong et al, 2011).…”
Section: Shanzhai Goes Global: Modularization and (Dis)respect For In...mentioning
confidence: 99%
“…MediaTek's turn-key solution not only provided competitive products to giant technology companies, such as Sony and Samsung, it also allowed mid-and smallsized mobile phone vendors to produce high-quality smartphones with much less capital investment and with shorter turnaround times than traditional methods (Chen, 2013;Rong et al, 2011). The market impact of MediaTek chipsets and its business model, which relied on modularization, was huge, leading to major financial losses for companies such as Texas Instruments (TI), a United States based semiconductor manufacturer (Wang, 2014). Modularization enabled shanzhai companies to be flexible enough to adapt to new technological developments and to add their own innovations (Jason Shay et al, 2020).…”
Section: Shanzhai Goes Global: Modularization and (Dis)respect For In...mentioning
confidence: 99%
“…The embedded software includes embedded operating systems, mobile apps, and middleware. In particular, IoT devices can be embedded further in other devices [17,19,27]. IoT monitored and detected information is invisibly embedded in the environment around users, results in the generation of big data in real-time, which is distributed, stored, processed, presented, and interpreted in a seamless, efficient, and easily understandable form [17,19,28].…”
Section: Internet Of Thingsmentioning
confidence: 99%
“…In addition to IoT-enabled environments, IoT technologies are commercialized by embedding IoT components in various interconnected smart products. IoT enables the evolution of various products such as smart home appliances, robots, drones, crewless cars, automated factory machines and business equipment, and many other innovative devices [2,19,21,26,27]. The smart environments and interconnected smart products can further enable cyber-physical convergence.…”
Section: Internet Of Thingsmentioning
confidence: 99%